THE NECESSITY OF ALTERNATIVE HISTORY ON GRAPHIC VIOLENCE AS CATHARSIS IN ONCE UPON A TIME IN HOLLYWOOD (2019) MOVIE - Fari, Dimas Muhammad Akbar Ramadhan Fari (IAIN Surakarta, 2025)
The depiction of graphic violence in movies is still quite debatable, whether it was necessary enough to be shown as they were believed to affect others to commit real-life violence. Quentin Tarantino, a movie director who grew up enjoying western, exploitation, and action movie genres, did not find any problem applying such elements as he believed it was nothing but one of the entertainment elements in movies. Being famous for his action-revenge movies, Tarantino once again proved to the audience how graphic violence can be one of the necessary aspects to be infused as a catharsis element through an alternative history narrative within his non-action-crime nor action-revenge genre movie under the title of Once Upon A Time In Hollywood (2019). To justify the graphic violence as catharsis through the audience's perspective, the writer applied the alternative history narrative theory and collected the data in the form of movie reviews on the Letterboxd website and comments on the YouTube website through qualitative content analysis. The results show how audiences justify the application of graphic violence through an alternative history narrative as a catharsis element that Tarantino adjusted.